(untitled) (Revista Internacional de Formação de Professores, 2025)
This study analyzed scientific productions to understand the methods used and origins of research on teacher education in Physical Education, aiming to assess their contributions to undergraduate programs. A literature review was conducted using SciELO, selecting 25 publications from 276 articles. Key research focuses include the connection between universities and schools, the role of teacher educators, the dominance of sports-related practical knowledge in training, professional knowledge for teaching, and reflections on the role of schools. Additionally, the court is highlighted as a space for knowledge construction